Literatur Review Tentang Early Warning Score (Meows) Untuk Deteksi Dini Kegawatdaruratan Maternitas Di Fasilitas Kesehatan Primer - Purwaningsih; Nisrina (STIKES Columbia Asia Medan, 2025)
The maternal mortality rate remains a significant global health challenge, particularly in developing countries. Timely detection of obstetric emergencies such as preeclampsia, sepsis, and postpartum hemorrhage is crucial to reducing delays in treatment. This literature review aims to analyze the implementation and effectiveness of the Modified Early Obstetric Warning Score (MEOWS) in primary healthcare settings. The review included 22 articles published between 2016 and 2023, identified through databases such as Scopus, PubMed, and ScienceDirect. Findings indicate that MEOWS is effective in detecting early signs of maternal deterioration, improving clinical decision-making, and preventing severe complications. However, challenges remain in adopting MEOWS in primary care due to limited training, lack of standardized protocols, and inadequate resources. The results highlight the need for capacity building, policy support, and contextual adaptation of MEOWS to optimize its use in community-based maternal care. This review suggests that the integration of MEOWS can strengthen obstetric triage systems and contribute to lowering maternal mortality rates in low-resource settings.